The Influence of Teaching Reading Islamic Narrative Stories toward Studentsâ€™ Social Behavior - Hidayat, Tawvicky (RADIANT: Journal of Applied, Social, and Education Studies, 2021)
In this millennium era, Indonesia faced moral crisis within the school or outside the school. They are accustomed to do bad behavior due to spiritual lack. Spiritual crisis happened because they were not given enough lessons about religion. However, teachers must provide good learning materials, so that the students can change their behavior. Even when teachers/lecturers teach English they must include religious knowledge in their teachings. Such as reading moral stories, giving good advices to students, telling about prophet stories, etc. Reading or telling story can affect moral, as the study held by Dr. Kang Lee and Colleagues that was recently published in the article â€Can Classic Moral Stories Promote Honesty in Childrenâ€. In that case, the researcher should study â€œThe Influence of Teaching Reading Islamic Narrative Stories Toward Studentsâ€™ Social Behaviorâ€. There are two research problems in this study. The first, is there any influence of using Reading Islamic Narrative Stories towards Social Behavior in intensive class IV semester IDIA Al-Amien Prenduan? The second, how significance does using Reading Islamic Narrative Stories towards Social Behavior in intensive class semester IV IDIA Al-Amien Prenduan? The research population of this study is the students of the intensive class IV semester IDIA Al-Amien Prenduan, they are 19 students. The main instrument used in this research is test, and the supporting instruments are observation and documentation. The tests were divided into pre-test and post-test. Since this study is quantitative, the researcher used statistical analysis as data analysis. The statistical formula which was used was t-test which was suitable with the research design, and it is one group pretest-posttest design. The research result shows that using Reading Islamic Narrative Stories towards Social Attitude in intensive class semester IV IDIA Al-Amien Prenduan with significance.